2019
DOI: 10.1111/aos.14155
|View full text |Cite
|
Sign up to set email alerts
|

Meibomian gland inversion: under‐recognized entity

Abstract: Objective: To describe a clinical entity of upper eyelid margin and meibomian gland inversion (MGI) sequential to meibomian gland dysfunction (MGD), in the absence of eyelash ptosis, trichiasis or manifest marginal entropion. We highlight its clinical features, surgical management and outcomes. Methods: We performed a retrospective analysis of symptomatic MGI cases refractory to conservative management who underwent surgery in our centre over a 4-year period. Anatomical correction, resolution of symptoms and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 22 publications
(25 reference statements)
0
29
0
Order By: Relevance
“…Therefore, surgical correction of marginal entropion could have additional benefits in improving dry eye syndrome and MGD. Similarly, Siah et al [ 23 ] reported improved signs and symptoms of MGD after corrective surgery for meibomian gland inversion. The effect of entropion repair for dry eye syndrome and MGD is thought to be sustained throughout the 5-month follow-up.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, surgical correction of marginal entropion could have additional benefits in improving dry eye syndrome and MGD. Similarly, Siah et al [ 23 ] reported improved signs and symptoms of MGD after corrective surgery for meibomian gland inversion. The effect of entropion repair for dry eye syndrome and MGD is thought to be sustained throughout the 5-month follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…Another major finding of the present study is the increase of LLT after surgical correction of marginal entropion. Siah et al [ 23 ] postulated that marginal entropion is a result of MGD, as the chronic subclinical inflammatory processes of MGD result in tarsal contraction and MG inversion. Our finding supposes that marginal entropion could also cause or exacerbate MGD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study done by Potemkin et al [1] had not examined changes in the status of MGD after the surgical correction of involutional eyelid malposition. Although the study done by Siah et al [19] noted improvement in ocular signs and symptoms after surgery, both of those previous studies [1,19] did not evaluate or compare the status of MGD before and after surgery.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study by Potemkin et al [1] showed that MGD was significantly worse in patients with involutional eyelid malposition, including entropion, ectropion, and punctal ectropion, than in controls. Another recent study done by Siah et al [19] presented a new clinical entity of meibomian gland inversion in the upper eyelid, which is associated with MGD. The results of these studies were similar to the findings of our study noticed preoperatively.…”
Section: Discussionmentioning
confidence: 99%